Interferência dos fatores físicos, químicos e do desenvolvimento do fungo simbionte de Atta sexdens rubropilosa Forel, 1908 (Hymenoptera: formicidae) na seleção de substratos e localização da desfolha - Noronha Junior, Newton Cavalcanti de [UNESP] (Universidade Estadual Paulista (Unesp), 2006)
The objective of this paper was to have a better understanding of plant-ant-symbiotic fungus interaction focusing on foraging behavior of Atta sexdens rubropilosa workers during plant selection. Physical and chemical substrate factors were approached which can have a role on foraging material selection for symbiotic fungus cultivation besides defoliating localization in artificial plants. Tested hypothesis was that besides chemical characteristics physical stimulus and leaves localization in a plant also play a very important role in substrate selection by A. sexdens rubropilosa workers. Different shape and thickness material was used (different leaves, paper leaves with different shapes and thickness impregnated in plant extract and artificial plants). The aim was to verify the existence of physical and chemical resistance, leaf palatability and defoliating localization. Wood plants Actinostemon communis, Alchornea triplinervea, Croton floribundus, Faramea cyanea, were offered to workers and evaluated 4 according to mechanical resistance of cut and palatability. Each plant was offered individually in big disc shape (2,5cm diameter), small disc shape (0,5cm diameter) and whole leaves. Other studies were carried out for detecting physical and chemical stimulus through simulated cuts and impregnation of plant extract in paper leaves with different thickness making it possible to evaluate the combinations between physical and chemical substrate characteristics. Defoliating localization in plants was studied when offering artificial plants with four levels where either wood plant or Ligustrum sp. leaves was attached. Defoliating intensity was measured by the number of fallen leaves by ants. In order to study wood plant attractiveness small disc shaped leaves (0,5cm diameter) were offered at the same time for ants in laboratory. The end of the experiment was determined either by the carrying... (Complete abstract, click electronics address below).
Keywords: Plantas - Seleção; Sauva (Formiga) - Comportamento; Leucoagaricus gongylophorus; Desfolhamento; Atta sexdens rubropilosa; Plant selection; Behavior; Defoliating